The Influence of Brand Image, Brand Equity, and Influencers on Yamaha Motorcycle Purchase Decisions among University Students - Bonanchya Rampow Tallamma; Amir Jaya; Jerliyen Pramita Londong (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
Previous research has reported mixed findings regarding the effectiveness of brand image and brand equity in shaping young consumers’ purchasing decisions in the digital era. This study examines the impact of brand image, brand equity, and influencers on Yamaha motorcycle purchasing decisions among university students, with a focus on identifying the most influential factors in contemporary digital marketing contexts. A quantitative method was applied through a survey of 96 Yamaha motorcycle users from Paulus Christian University of Indonesia, Makassar. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results reveal an unexpected pattern: brand image (t-statistic = 1.069, p = 0.285) and brand equity (t-statistic = 1.142, p = 0.253) did not have a significant effect on purchase decisions. In contrast, influencers exerted a strong and statistically significant positive influence (t-statistic = 6.021, p = 0.000, f² = 0.504), explaining 52.3% of the variance in purchase decisions. These results challenge traditional assumptions regarding brand power and indicate a paradigm shift from brand-centered to social influence-centered marketing among digital-native consumers. From a practical standpoint, the findings suggest that Yamaha and other automotive companies should reallocate marketing resources from conventional brand image enhancement toward more authentic and personalized influencer marketing strategies targeting the student segment.